Pengolahan Limbah Cair Rumah Sakit secara Sonochemical - Laila Kusuma; Darmadi Darmadi; Adisalamun Adisalamun (Jurnal Litbang Industri, 2017)
Hospital as a service provider has an important role in human life, especially for people who are experiencing physical and mental disorders. Various types of diseases and therapies performed in hospitals has made it as one of the producers of hazardous and infectious waste that requires special handling and processing so as not to pollute the water, soil, and air environment. Hospital wastewater treatment was conducted to determine the ability of sonochemical method to reduce level of Chemical Oxygen Demand (COD) and determine the optimum conditions of the parameters used by the design of Response Surface Methodology Box-Behnken. The parameters that affected this process was the concentration of hydrogen peroxide (H2O2), pH, and reaction time. The Waste used was taken from the waste water treatment plant in Zainoel Abidin General Hospital in Banda Aceh with COD value 260.65 ppm. The optimum conditions of this treatment process occured at pH 2, H2O2 concentration 500 ppm, and reaction time 119.98 minutes with reduction of COD was 81.88%.ABSTRAKRumah sakit sebagai penyedia layanan jasa memegang peranan cukup penting dalam kehidupan manusia, terutama bagi orang-orang yang sedang mengalami gangguan fisik dan mental. Berbagai jenis penyakit dan terapi yang dilakukan di rumah sakit telah menjadikannya sebagai salah satu penghasil limbah berbahaya dan infeksius yang memerlukan penanganan dan pengolahan khusus agar tidak mencemari lingkungan yaitu air, tanah dan udara. Pengolahan limbah cair rumah sakit dilakukan untuk mengetahui kemampuan metode sonochemical dalam menurunkan kadar Chemical Oxygen Demand (COD) dan menentukan kondisi optimum dari parameter yang digunakan berdasarkan disain Response Surface Methodology Box-Behnken. Parameter yang mempengaruhi proses ini adalah konsentrasi hidrogen peroksida (H2O2), pH, dan waktu reaksi. Limbah yang digunakan diambil dari instalasi pengolahan air limbah di Rumah Sakit Umum Zainoel Abidin Kota Banda Aceh dengan nilai COD sebesar 260,65 ppm. Kondisi optimum dari proses pengolahan terjadi pada pH 2, konsentrasi H2O2 500 ppm, dan waktu reaksi 119,98 menit dengan penurunan COD sebesar 81,88 %